Conceptions of nursing staff about psychiatric care in general hospital - Leila Mariza Hildebrandt; João Fernando Marcolan (Universidade Federal do Ceará, 2016)
Objective: to understand the concepts of Nursing professionals about the hospitalization of people with mental disorders admitted to psychiatric units of general hospitals. Methods: this is a qualitative research developed in three general hospitals. The data collection was carried out through semi-structured interviews and systematic observation. Thirty Nursing professionals were interviewed. The data analysis was based on content analysis. Results: issues concerning fragility were identified in the training of Nursing professionals, prejudices related to psychiatric care in general hospitals and presence of lunatic characteristics in the surveyed institutions. Conclusion: investments are needed in the training of nursing professionals to qualify the assistance and social interventions to minimize the prejudice against people with mental disorder.